The Effect of Students’ Learning Motivation toward Retention in Biology Learning Using Augmented Reality-based Media - Tamam, Badrud; Fikriyah, Aida (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2024)
This research aims to examine the effect of students’ learning motivation to retention in biology learning. This research is included in quantitative research. The research sample was 56 students. To measure learning motivation, the ARCS (Attention, Relevance, Confidence and Satisfaction) motivation questionnaire was used which was adapted from Keller (2010) with a total of 36 statements. Retention was measured using an essay test which was carried out 2 weeks after the posttest. Student answers were then measured using Hart's (1994) rubric. A simple linear regression analysis was carried out to see the effect of students’ learning motivation toward retention. The results of data analysis show that there is a significant effect of students’ learning motivation toward the retention. Based on the regression results, it is known that the R value is 0.654, which indicates that there is a correlation in which a strong relationship between motivation and retention. Motivation has a contribution of 42.8% to retention and 57.2% is influenced by other factors. It can be concluded that learning motivation can encourage working memory performance so that the flow of information can be processed in the long-term memory.